SENTIMENT ANALYSIS OF BALI 2024 GOVERNOR CANDIDATES ON X APPLICATION USING SUPPORT VECTOR MACHINE METHOD - Deanika, I Gusti Ngurah Agung; Udayana, I Putu Agus Eka Darma; Setiawan, I Nyoman Anom Fajaraditya; Yanti, Christina Purnama; Pratistha, Indra (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This research is motivated by the 2024 Bali PILKADA which will be held simulataneously in each region on November 27, 2024 to elect local leader, such as Governor, regents, and mayors. The existence of this Bali PILKADA, attracted the author to conduct research analyzing public sentiment towards candidates for Governor and Deputy Governor who will run in the 2024 Bali PILKADA. Data was collected from application X (formely twitter). Application X was chosen because of its ability to connect all users to communicate with each other through text messages “tweet” and very quickly to raise topics that are being discussed by the public. This study uses SVM method of classify the sentiment of the community in the from of positive, negative, and neutral and seek high accuracy value. Data was collected by crawling tweet text using Python code on Google Collab which resulted in 1010 raw data entries then continued with the preprocessing stage, which involved data cleaning for testing purposes. The data testing was conducted with three scenarios from the 1010 data, resulting in the highest accuracy rate of 79% and 302 data of tweets as positve sentiment, 462 data as negative sentiment, and 246 data as neutral sentiment.